Optimum airspace sectorisation with hexagonal cell-based workload modelling - Tong, Grace Jing Ying (2016)
The increase in demand for air travel, and burgeoning emphasis on aviation safety has increased the importance of well-distributed workload on Air Traffic Controllers (ATCos), so that they have optimal concentration on tasks at hand. In this aspect, increasing amount of research are being conducted by aviation authorities and institutes on new software and optimization models. These researches are carried out in both flight routing procedures and sectorisation. One particular area of focus in the research on sectorisation is hexagonal cell based modeling. The objective of hexagonal cell based modeling is to enable use of optimization techniques for airspace sectorisation. This research adapts the model introduced by Yousefi. An amalgation of Yousefi’s models and common constraints in air traffic sectorisation are further explored and the effectiveness of the model was studied. Findings demonstrate the feasibility of Yousefi’s hexagonal cell-based modeling in sectorisation using Genetic Algorithm.